FORMULATION OPTIMIZATION OF FENUGREEK EXTRACT LOADED NANO-STRUCTURED LIPID-DRUG-CARRIER FOR EFFECTIVE ORAL DELIVERY - ADITI AGRAWAL; PRAKASH K SONI; REENA SONI; SURESH K PASWAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present work focused on designing, optimizing, and evaluating solid lipid nanoparticles (SLNs) for the oral delivery of fenugreek extract (FE) to achieve enhanced systemic bioavailability, higher gastrointestinal absorption, and sustained release kinetics. Methods: A Box-Behnken statistical design was implemented to optimize FE-SLNs formulation by systematically varying lipid (compritol 888 ATO), surfactant (polyvinyl alcohol), and homogenization speed as processing parameter. Critical quality attributes including mean particle size, polydispersity index (PDI), surface charge (zeta potential), encapsulation efficiency (%EE), and release behavior (% cumulative drug release [CDR]) were analyzed. The final formulation was further characterized by advanced analytical techniques (transmission electron microscopy, differential scanning calorimeter) and evaluated for ex vivo intestinal permeation. Results: The optimized FE-SLNs demonstrated favorable characteristics, average diameter (460 nm), uniform distribution (PDI 0.233), surface charge (−14.1 mV), and %EE (47.56%). In vitro studies showed %CDR (79.66% over 12 h). Permeation assessments revealed significantly enhanced absorption compared to FE solution, with permeability coefficients increasing from 2.9×10−3 cm/h (FE solution) to 6.3×10−3 cm/h (developed formulation). Conclusion: The developed FE-SLNs system exhibited optimal physicochemical properties and enhanced absorption potential, demonstrating its successful formulation. The sustained release profile following Higuchi kinetics suggested that these nanoparticles could serve as an effective platform for oral administration of natural bioactives.